2007
DOI: 10.1177/193229680700100102
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Assessing Insulin Dose Adjustments by Patients with Diabetes

Abstract: Background:Insulin treated diabetic patients often do not adjust their insulin doses. We developed a method to provide a quantitative and qualitative assessment of this behavior. Methods:Fourteen patients provided logbook pages of their self-monitoring of blood glucose (SMBG) data and insulin doses. We compared the actual decisions of patients in real-life to what they would decide on the same SMBG, as an a posteriori exercise. We also compared these decisions and those proposed by 6 diabetologists on the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 11 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…Problems with carbohydrate counting accuracy and with deviations from the prescribed insulin bolus regimen have been well documented among patients with T1D. 26,27 Use of a bolus advisor appears to modestly reduce HbA1c and glycemic variability in a longitudinal observational study, but the degree to which accurate carbohydrate counting and accurate bolusing relate to overall glycemic control remains to be determined. 28 Finally, the present study only evaluated the relationship between BOLUS and mean glycemic control, with no attention given to glycemic variability, which has been the subject of much interest as a potential predictor for acute and chronic complications in T1D.…”
Section: Discussionmentioning
confidence: 99%
“…Problems with carbohydrate counting accuracy and with deviations from the prescribed insulin bolus regimen have been well documented among patients with T1D. 26,27 Use of a bolus advisor appears to modestly reduce HbA1c and glycemic variability in a longitudinal observational study, but the degree to which accurate carbohydrate counting and accurate bolusing relate to overall glycemic control remains to be determined. 28 Finally, the present study only evaluated the relationship between BOLUS and mean glycemic control, with no attention given to glycemic variability, which has been the subject of much interest as a potential predictor for acute and chronic complications in T1D.…”
Section: Discussionmentioning
confidence: 99%
“…Choosing a dose also involves including a self-monitored glucose level to calculate any correction dose. The complexity of choosing and calculating premeal doses by accounting for variations in meal sizes and composition and for physical activity is often overwhelming and can be compounded by fears of hypoglycemia (21).…”
Section: Treatment Management and Adherencementioning
confidence: 99%
“…These ADA guidelines note the particular importance of SMBG for people with diabetes who use multiple-dose insulin or insulin pump therapy, 13 as they use SMBG results to adjust their insulin dose. 14 In the past, a number of analyses have demonstrated that inaccurate BGMS results can lead to errors in insulin dosing. 3,4,7 As more recently published, errors in blood glucose readings may result in contraindicated treatment decisions.…”
Section: Discussionmentioning
confidence: 99%